For the real coffee guzzler - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Coffee: Recent Developments Edited by RJ Clarke & OG Vitzthum, World Agriculture Series, Blackwell Science, 2001. 272 pp. ISBN 0 632 05553 7 GBP 85 Euro 142